ANALISIS PERBANDINGAN MODEL ALTMAN Z-SCORE, SPRINGATE, ZMIJEWSKI DAN GROVER DALAM MEMPREDIKSI FINANCIAL DISTRESS - Norma Gupita; Sri Widiyati Soemoedipiro; Nina Woelan Soebroto (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2020)
This study aims to determine whether there are differences in the Altman Z-Score, Springate, Zmijewski and Grover models in predicting financial distress in infrastructure sector companies listed on the IDX in 2015-2019. By using a purposive sampling technique. The data analysis technique used non-parametric statistics, the Wilcoxon signed ranks test and the prediction model accuracy test without the condition that the data had to be normally distributed. This study compares four financial distress prediction models using descriptive statistical analysis, classical assumption test, and Wilcoxon signed ranks test through the SPSS program. The results showed that there was a difference between the Altman Z-Score, Springate and Grover. The model that has the highest level of accuracy is Springate with an accuracy rate of 83.33%.